Silicon-carbon negative electrode material based on nanocellulose as well as preparation method and application of silicon-carbon negative electrode material
Through the preparation method of silicon-carbon negative electrode material based on nanocellulose, the problems of difficult nanostructure design, low first efficiency and poor cycle stability in lithium-ion batteries are solved, and the structure of the material is spherical, porous, and excellent electrochemical performance, with industrial prospects.
Patent Information
- Application Number
- CN202510091534.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Existing silicon-based materials have problems such as difficulty in nanostructure design, low first efficiency and poor cycle stability in lithium-ion batteries.
Through the preparation method of silicon carbon anode material based on nanocellulose, nanocellulose is prepared by a short process, and the granulation preparation of silicon carbon material is realized through a one-pot process to form a multi-stage coated structure and a hybrid conductive network to alleviate the volume changes of the silicon source and improve electrochemical performance.
The structure of silicon carbon negative electrode material is spherical, porous and dense, with excellent electrochemical performance, simple and easy to batch amplify, and has industrial prospects, which improves the charging specific capacitance and first-effect of lithium-ion batteries, and ensures good cycle stability performance.
Smart Images

Figure CN119911895A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a method for preparing a silicon-carbon negative electrode material. Background Art
[0002] Cellulose is the most widely distributed and abundant polysaccharide in nature, accounting for more than 50% of the carbon content in the plant kingdom. It is one of the main sources of renewable materials and has a wide range of applications in many fields, including energy storage. Nanocellulose is a nanoscale cellulose material with excellent mechanical strength, high crystallinity, high aspect ratio, large specific surface area, modifiability and other advantages, and can be used to prepare high-performance nanocomposites. The highly ordered hydrogen bond network structure of cellulose makes it difficult to dissolve cellulose in conventional solvents, thus limiting further development and large-scale application. Existing cellulose dissolution systems have problems such as excessive degradation, non-recyclability, and difficulty in depolymerization. There is an urgent need to develop a new nanocellulose hydrolysis process.
[0003] With the widespread application of lithium-ion batteries in new energy vehicles, low-altitude economy, portable electronics, and large-scale energy storage, high energy density and high rate characteristics have become the future development trend of batteries. The performance of negative electrode materials directly determines the performance of lithium batteries. At present, traditional graphite is the main negative electrode material for lithium-ion batteries, which is close to its theoretical specific capacity and difficult to meet the performance requirements of high-energy density batteries for high-specific capacity negative electrode materials. Silicon-based materials have advantages such as high capacity and suitable lithium insertion and extraction potential, and have good prospects for graphite replacement, but their large volume expansion and poor conductivity are still key technical difficulties that restrict their large-scale application. The use of nanocellulose's high mechanical strength, modifiability, high aspect ratio and high carbonization conductivity, combined with silicon-based materials to prepare high-performance silicon-carbon materials has attracted widespread attention.
[0004] The patent CN117525366A previously disclosed by this team discloses a new type of silicon-based negative electrode material and its preparation method, which is prepared by mixing organic carbon source, carbon nanotubes, adhesive, etc. into a solution, spray drying and sintering to obtain a porous carbon material, then adding the porous carbon material and nano-silicon powder into a lithium fluoride conductive solution, vacuum rotary evaporation sintering to obtain a silicon-carbon precursor with nano-silicon deposited inside the porous carbon, and then adding the silicon-carbon precursor into a nanocellulose / ionic liquid solution, stirring, drying and calcining to obtain a new type of silicon-based negative electrode material with a multi-layer composite coating structure. This patent adopts a three-step sintering route, which is long and energy-consuming. After the porous carbon and nano-silicon are stirred in the solution, the effective deposition inside the nano-silicon cannot be guaranteed during the rotary evaporation process, and there are surface deposition and agglomeration phenomena. After the nanocellulose and silicon-carbon precursor are mixed, there is a risk of oxidation of nano-silicon during the high-temperature blast drying process, and it is difficult to ensure that the nanocellulose cracked carbon is deposited on the surface of the silicon-carbon precursor to form a uniformly coated carbon layer during the carbonization process. The patent with publication number CN114824234A discloses a silicon-carbon composite material and its preparation method and application, wherein a nanocellulose solution, a silicon source and a coupling agent are mixed, and the nanocellulose and the silicon source are combined by the coupling agent so that the nanocellulose can be tightly wrapped on the surface of the silicon source, and then sintered after centrifugation. The nanocellulose forms a carbon fiber layer on the surface of the silicon source, which plays a role in buffering volume expansion. The patent has a simple process route, and a complete and uniform carbon coating layer cannot be formed by simply coating and carbonizing the nanocellulose. The effect of buffering the volume expansion of the silicon source is limited, and the side reaction between the electrolyte and the silicon source surface cannot be well inhibited. Summary of the invention
[0005] In order to solve the technical problems of difficult design of nanostructures, low initial efficiency and poor cycle stability of silicon-based materials, the present invention proposes a silicon-carbon negative electrode material based on nanocellulose and its preparation method and application. The preparation method obtains nanocellulose through a short process and realizes the granulation preparation of silicon-carbon materials through a one-pot process. The obtained silicon-carbon negative electrode has the advantages of spherical structure, complete structure, porous and dense structure, and good electrochemical performance. The process is simple and easy to scale up in batches. It has industrial prospects and provides technical references for technical improvement and product upgrades of new silicon-carbon negative electrode materials for lithium-ion batteries.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0007] Nanocellulose is firstly obtained by physical sand grinding, peeling and crushing, and then acid hydrolyzing cellulose with the aid of ionic liquid, which has the advantages of short process and low cost. Carbon source, conductive agent, coupling agent, silicon source, etc. are added to the obtained nanocellulose colloidal solution in sequence to form a uniform mixed solution, and a uniform nano-structured silicon-carbon precursor is formed by spray granulation, which is carbonized to form a uniform surface coating layer. The prepared material has a multi-level coating structure and a conductive network that penetrates the material, ensuring the structural stability of the material and the fast carrier transport performance.
[0008] The preparation method of silicon-carbon negative electrode material based on nanocellulose, the steps are as follows:
[0009] (1) Cellulose is added to deionized water, stirred and treated with high-energy ultrasound, and then sand-milled to obtain dispersion A. High-energy ultrasound promotes the separation of cellulose lamellae and achieves preliminary separation; the sand-milling process physically peels off the cellulose lamellae and promotes the breaking of cellulose glycosidic bonds.
[0010] (2) Adding a hydrolysis catalyst and an ionic liquid to dispersion A, adding an acid solution to adjust the pH to 1.0-2.0, and obtaining dispersion B after heating and stirring. The catalyst is a transition metal salt that can selectively degrade cellulose to generate an amorphous structure with a microcrystalline size. The ionic liquid can destroy the complex structure of cellulose through swelling, weaken the hydrogen bonding force, and promote the cleavage of glycosidic bonds.
[0011] (3) After adjusting the pH of dispersion B to 3.0-4.0, a carbon source and a conductive agent are added; then a coupling agent and a silicon source are added, and dispersion C is obtained after dispersion. By adjusting the pH of the solution, the protonation of the coated carbon source can be promoted, and the combination between the carbon source and nano-silicon can be promoted to form a stable carbon layer. The introduction of the coupling agent can promote the cross-linking of nanocellulose, the coated carbon source and the silicon source, and promote the combination of nanocellulose and the coated carbon source with the surface of the silicon source.
[0012] (4) The dispersion C is spray dried to obtain a silicon-carbon precursor D. The spray drying process promotes the formation of nanostructures by granulation of silicon source, carbon source, nanocellulose, etc., so that the carbon source forms a stable carbon layer on the silicon surface, and the nanocellulose is evenly distributed from the inside to the outside of the nanostructure, forming a uniform conductive network structure.
[0013] (5) The silicon-carbon precursor D is sintered in nitrogen and carbonized by vapor deposition to obtain a silicon-carbon product E; then, after washing and drying, a silicon-carbon negative electrode material based on nanocellulose is obtained. A plasma-enhanced vapor deposition furnace can be used for high-temperature carbonization sintering, first using nitrogen for sintering, and then introducing a deposition gas source to obtain a spherical silicon-carbon product E. The carbonization process forms a stable amorphous carbon coating layer. On the one hand, nanocellulose forms a microcrystalline carbon layer to achieve carbon coating, and on the other hand, the conductive material couples to form a conductive network. Finally, the transition metal catalytic sites in the catalyst are used to promote the formation of a deposited carbon film on the surface of the nanostructure, which improves the material's anti-expansion ability while inhibiting side reactions between the electrolyte and the material surface, reducing irreversible lithium loss. In addition, by washing, impurities such as heteroatom salts remaining on the surface and inside the material are washed away, further improving the electrochemical activity of the material.
[0014] In the above step (1), the cellulose is any one of cotton cellulose, wheat straw cellulose and corn straw cellulose, with a purity of 90-95% and a particle size D50 of 30-65 μm; and the high-energy ultrasonic treatment time is 1-4 h.
[0015] Furthermore, the sand grinding treatment time in step (1) is 1-4 hours, and the particle size of the zirconium oxide beads used for sand grinding is any one of 0.1 mm, 0.2 mm and 0.3 mm.
[0016] In the above step (2), the hydrolysis catalyst is any one of zinc chloride, ferric chloride, nickel chloride, cobalt chloride, zinc nitrate, nickel nitrate, cobalt acetate and nickel acetate; the ionic liquid is any one of 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium hydrogen sulfate and 3-ethoxymethyl-1-methylimine hydrogen sulfate.
[0017] Furthermore, the mass ratio of the hydrolysis catalyst to the ionic liquid is (2-5):(2-3); and the acid solution is any one of oxalic acid, acetic acid, citric acid, sulfuric acid, hydrochloric acid and nitric acid.
[0018] The temperature of the heating and stirring treatment in the above step (2) is 60-90°C and the time is 2-8h.
[0019] The mass ratio of cellulose, carbon source, conductive agent, coupling agent and silicon source in the dispersion C of the above step (3) is 5:(6-8):(0.1-0.25):(0.15-0.5):(7.5-15); the concentration of the carbon source is 30-40 g / L.
[0020] Furthermore, in the above step (3), the carbon source is any one of chitosan, citric acid, phytic acid, sucrose, polyethylene glycol, phenolic resin, polydopamine and fructose; the conductive agent is any one of single-walled or multi-walled carbon nanotubes, hydroxyl carbon nanotubes, carboxyl carbon nanotubes, graphene oxide, graphene, conductive carbon black and acetylene black; the coupling agent is any one of γ-aminopropyltriethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, N1-(3-(trimethoxysilyl)propyl)ethane-1,2-diamine, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and hexadecyltrimethylammonium bromide; the silicon source is at least one of silicon oxide, nano silicon and micro silicon, wherein the silicon oxide particle size D50: 3-5μm, the nano silicon particle size D50: 50-150nm, and the micro silicon particle size D50: 0.5-2μm.
[0021] In the above step (4), the spray drying spray pressure is 0.15-0.25Mpa, and the inlet temperature is 160-200°C.
[0022] In the above step (5), the sintering in nitrogen is carried out by heating the temperature to 700-1000°C at a heating rate of 3-15°C / min and keeping the temperature for 2-6h; the deposition gas source in the vapor deposition carbonization sintering is a mixed gas composed of at least one of acetylene, ethylene, methane and ethane and nitrogen, and the temperature of the vapor deposition carbonization sintering is 500-800°C and the time is 0.5-2h.
[0023] Furthermore, in step (5), the solid content of the product E during the washing process is 10-20%, the washing time is 0.5-1 h, and the number of washing times is 2-4 times.
[0024] The silicon-carbon negative electrode material prepared by the above-mentioned preparation method has a pore structure from the inside to the outside.
[0025] A lithium-ion battery comprises the above-mentioned silicon-carbon negative electrode material.
[0026] The beneficial effects produced by the present invention are:
[0027] (1) The present invention prepares nanocellulose and its colloidal solution through low cost and short process, disperses cellulose in deionized water, and realizes the exfoliation of cellulose sheets and the cleavage of glycosidic bonds through high-energy ultrasound and sand milling physical crushing process; by adding acid, ionic liquid and hydrolysis catalyst, the strong hydrogen bond force between cellulose is weakened by the swelling effect of ionic liquid, and the dissociation and glycosidic bond cleavage process under acidic conditions is strengthened, and the cellulose is further depolymerized and bond-broken, and fragmented to form a uniform and stable nanocellulose suspension; then the suspension is diluted and the pH is adjusted, and a coating carbon source, a conductive agent, a coupling agent and a silicon source are added in sequence, and by protonating part of the carbon source and promoting the organic combination of the carbon source, nanocellulose and the silicon source surface under the induction of the coupling agent, a coating carbon layer is formed. Spray drying is used to achieve nano-micro spheroidization between silicon and other materials, promote the stable coating of carbon source on the silicon surface and particles, and form a conductive network from the inside to the outside; during the carbonization process, nanocellulose is cracked to form a cellulose microcrystalline carbon layer or conductive fiber, which not only plays a coating role but also forms a mixed conductive channel with the conductive agent component. The catalyst transition metal sites contained on the surface and inside of the material can induce the deposition of carbon source to form a carbon film, carbon tube or mixed coating layer on the surface of the material, further improving the material structure and performance stability.
[0028] (2) The nanocellulose-based silicon-carbon negative electrode material prepared by the present invention has a multi-level coating structure and a mixed conductive network, and also has a pore structure from the inside to the outside. The multi-level coating structure mainly includes the amorphous carbon layer formed by the connection of the dissolved carbon source on the silicon surface, the decomposition of the nanocellulose during the carbonization process, and the deposited carbon layer during the plasma enhanced vapor deposition process. The mixed conductive network includes a conductive agent, conductive fibers formed by the carbonization of nanocellulose, etc. The conductive agent is adsorbed on the surface of a single particle silicon source, and a conductive skeleton network structure from the inside to the outside is formed during the spray drying ball formation process. Finally, some carbon nanotubes are also grown in situ in the deposited carbon layer to further improve the conductivity. In addition, certain pores are formed inside the spray drying nano-micro ball formation process, and a certain space is released during the decomposition process of the carbonized nanocellulose, further forming a pore structure. The multi-level coating and pore structure can effectively alleviate the volume change of the silicon source during the lithium insertion and extraction process, and improve the structural stability; the multi-level conductive network improves the material's electronic transmission efficiency and high electrochemical activity, thereby improving the material's charge specific capacitance and first efficiency, and ensuring its good cycle stability.
[0029] (3) The process of the present invention is simple and easy to scale up in batches, and has industrial prospects, providing a technical reference for the technical improvement and product upgrade of new silicon-carbon negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is a flow chart of the method for preparing nanocellulose and silicon-carbon negative electrode materials of the present invention.
[0032] Figure 2 This is a scanning electron microscope image of the nanocellulose-based silicon-carbon negative electrode material obtained in Example 1.
[0033] Figure 3 This is a scanning electron microscope image of the nanocellulose-based silicon-carbon negative electrode material obtained in Example 1.
[0034] Figure 4 This is a comparison chart of the first charge and discharge of the silicon-carbon negative electrode materials obtained in Example 1 and Comparative Examples 1 and 2.
[0035] Figure 5 It is a comparison chart of the cycle stability of the silicon-carbon negative electrode materials obtained in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment is as follows: Figure 1 As shown, the steps are as follows:
[0039] (1) 5 g of cotton cellulose (purity 95%, particle size D50 30 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 1 h, and then treated in a sand mill with 0.3 mm zirconium oxide beads for 2 h to obtain dispersion A;
[0040] (2) adding 0.2 g of zinc chloride and 0.2 g of 1-ethyl-3-methylimidazolium acetate to dispersion A, adding oxalic acid solution to adjust the pH to 1.0, and stirring at 60° C. for 2 h to obtain dispersion B;
[0041] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 6 g of chitosan and 0.1 g of single-walled carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.15 g of γ-aminopropyltriethoxysilane and 15 g of nano-silicon (particle size D50: 50-150 nm) were added in sequence, ultrasonically dispersed uniformly, and stirred at room temperature for 2 h to obtain dispersion C;
[0042] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 180° C., to obtain a silicon-carbon precursor D;
[0043] (5) A plasma enhanced vapor deposition furnace was used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 5°C / min. The product was carbonized at 800°C for 2h, and then a 5% acetylene / nitrogen mixed gas was introduced and deposited at 500°C for 0.5h to obtain a spherical silicon-carbon product E. The product was then dispersed in deionized water and the solid content was adjusted to 10%. The product was washed three times for 0.5h each time, filtered and dried to obtain a silicon-carbon negative electrode material.
[0044] The microstructure of the prepared samples was measured using a Japanese JEOL JSM-7900F scanning electron microscope. Figure 2 It can be seen that the prepared silicon-carbon material has a good nano-micro spherical structure and is rich in porous structure inside, which can ensure good infiltration of the electrolyte and greatly promote ion transport. The lithium insertion and extraction process has the function of buffering the volume change of silicon.
[0045] Example 2
[0046] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0047] (1) 5 g of wheat straw cellulose (purity 90%, particle size D50 65 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 2 h, and then treated in a sand mill with 0.2 mm zirconium oxide beads for 1 h to obtain dispersion A;
[0048] (2) adding 0.2 g of ferric chloride and 0.25 g of 3-ethoxymethyl-1-methylimine hydrogen sulfate to dispersion A, adding acetic acid solution to adjust the pH to 2.0, and stirring at 70° C. for 3 h to obtain dispersion B;
[0049] (3) Ammonia water was added dropwise to adjust the pH to 4.0, and 6 g of citric acid and 0.15 g of multi-walled carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.2 g of 3-glycidyloxypropylmethyldiethoxysilane and 15 g of silicon dioxide (particle size D50: 3-5 μm) were added in sequence and ultrasonically dispersed uniformly, and stirred at room temperature for 6 h to obtain dispersion C;
[0050] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.15 MPa and the inlet temperature to 160° C., to obtain a silicon-carbon precursor D;
[0051] (5) A plasma enhanced vapor deposition furnace is used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 10°C / min. The product is carbonized at 700°C for 4 hours, and then a 5% ethylene / nitrogen mixed gas is introduced and deposited at 600°C for 1 hour to obtain a spherical silicon-carbon product E. The product is then dispersed in deionized water, the solid content is adjusted to 15%, and the product is washed twice for 1 hour each time. The product is then filtered and dried to obtain a silicon-carbon negative electrode material.
[0052] Example 3
[0053] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0054] (1) 5 g corn straw cellulose (purity 92.5%, particle size D50 40 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 2 h, and then treated in a sand mill with 0.1 mm zirconium oxide beads for 3 h to obtain dispersion A;
[0055] (2) adding 0.5 g of nickel chloride and 0.3 g of 1-allyl-3-methylimidazolium chloride to dispersion A, adding citric acid solution to adjust the pH to 1.0, and stirring at 80° C. for 5 h to obtain dispersion B;
[0056] (3) Ammonia water was added dropwise to adjust the pH to 3.5, and 8 g of phytic acid and 0.2 g of hydroxy carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.25 g of N1-(3-(trimethoxysilyl)propyl)ethane-1,2-diamine and 15 g of micron silicon (particle size D50: 0.5-2 μm) were added in sequence, ultrasonically dispersed uniformly, and stirred at room temperature for 8 h to obtain dispersion C;
[0057] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.25 MPa and the inlet temperature to 170° C., to obtain a silicon-carbon precursor D;
[0058] (5) A plasma enhanced vapor deposition furnace was used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 3°C / min. The product was carbonized at 750°C for 4 hours, and then a 5% methane / nitrogen mixed gas was introduced and deposited at 700°C for 1.5 hours to obtain a spherical silicon-carbon product E. The product was then dispersed in deionized water, the solid content was adjusted to 20%, and the product was washed four times for 0.5 hours each time. The product was then filtered and dried to obtain a silicon-carbon negative electrode material.
[0059] Example 4
[0060] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0061] (1) 5 g corn straw cellulose (purity 90%, particle size D50 50 μm) was added to 200 mL deionized water, stirred and treated with high-energy ultrasound for 3 h, and then treated in a sand mill with 0.2 mm zirconium oxide beads for 4 h to obtain dispersion A;
[0062] (2) adding 0.2 g of cobalt chloride and 0.2 g of 1-butyl 3-methylimidazolium chloride to dispersion A, adding sulfuric acid solution to adjust the pH to 2.0, and stirring at 90° C. for 6 h to obtain dispersion B;
[0063] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 8 g of sucrose and 0.15 g of carboxyl carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.5 g of 3-aminopropyltrimethoxysilane and 15 g of silicon dioxide (particle size D50: 3-5 μm) were added in sequence and ultrasonically dispersed uniformly, and stirred at room temperature for 2 h to obtain dispersion C;
[0064] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 190° C., to obtain a silicon-carbon precursor D;
[0065] (5) A plasma enhanced vapor deposition furnace is used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 15°C / min, and carbonization is performed at 900°C for 2 hours. Then, a 5% ethane / nitrogen mixed gas is introduced and deposited at 800°C for 2 hours to obtain a spherical silicon-carbon product E. The spherical silicon-carbon product E is then dispersed in deionized water, the solid content is adjusted to 20%, and the product is washed twice for 1 hour each time. The product is then filtered and dried to obtain a silicon-carbon negative electrode material.
[0066] Example 5
[0067] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0068] (1) 5 g of cotton cellulose (purity 95%, particle size D50 65 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 4 h, and then treated in a sand mill with 0.2 mm zirconium oxide beads for 4 h to obtain dispersion A;
[0069] (2) adding 0.2 g of cobalt chloride and 0.2 g of 1-butyl 3-methylimidazolium chloride to dispersion A, adding sulfuric acid solution to adjust the pH to 2.0, and stirring at 90° C. for 6 h to obtain dispersion B;
[0070] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 8 g of polyethylene glycol and 0.15 g of graphene oxide were added in sequence and ultrasonically dispersed uniformly; then 0.3 g of 3-aminopropyltriethoxysilane and 15 g of nano-silicon (particle size D50: 50-150 nm) were added in sequence and ultrasonically dispersed uniformly, and stirred at room temperature for 3 h to obtain dispersion C;
[0071] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.15 MPa and the inlet temperature to 200° C., to obtain a silicon-carbon precursor D;
[0072] (5) A plasma enhanced vapor deposition furnace is used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 12°C / min. The product is carbonized at 1000°C for 3 hours, and then a 5% acetylene / nitrogen mixed gas is introduced and deposited at 600°C for 1 hour to obtain a spherical silicon-carbon product E. The product is then dispersed in deionized water, the solid content is adjusted to 15%, and the product is washed three times for 0.5 hours each time. The product is then filtered and dried to obtain a silicon-carbon negative electrode material.
[0073] Example 6
[0074] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0075] (1) 5 g corn straw cellulose (purity 90%, particle size D50 30 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 4 h, and then treated in a sand mill with 0.3 mm zirconium oxide beads for 2 h to obtain dispersion A;
[0076] (2) adding 0.2 g of nickel nitrate and 0.25 g of 3-ethoxymethyl-1-methylimine hydrogen sulfate to dispersion A, adding nitric acid solution to adjust the pH to 1.0, and stirring at 80° C. for 4 h to obtain dispersion B;
[0077] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 6 g of phenolic resin and 0.2 g of graphene were added in sequence and ultrasonically dispersed uniformly; then 0.2 g of hexadecyltrimethylammonium bromide, 7.5 g of silicon dioxide (particle size D50: 3-5 μm) and 7.5 g of nano-silicon (particle size D50: 50-150 nm) were added in sequence and ultrasonically dispersed uniformly, and stirred at room temperature for 4 h to obtain dispersion C;
[0078] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 180° C., to obtain a silicon-carbon precursor D;
[0079] (5) A plasma enhanced vapor deposition furnace was used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 6°C / min. The product was carbonized at 800°C for 5 h, and then a 5% acetylene / nitrogen mixed gas was introduced and deposited at 600°C for 1.5 h to obtain a spherical silicon-carbon product E. The product was then dispersed in deionized water, the solid content was adjusted to 10%, and the product was washed three times for 1 h each time. The product was then filtered and dried to obtain a silicon-carbon negative electrode material.
[0080] Example 7
[0081] The preparation method of the nanocellulose-based silicon-carbon negative electrode material of this embodiment comprises the following steps:
[0082] (1) 5 g of wheat straw cellulose (purity 95%, particle size D50 65 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 2 h, and then treated in a sand mill with 0.2 mm zirconium oxide beads for 1.5 h to obtain dispersion A;
[0083] (2) adding 0.2 g of cobalt acetate and 0.2 g of 1-ethyl-3-methylimidazolium acetate to dispersion A, adding sulfuric acid solution to adjust the pH to 1.5, and stirring at 70° C. for 5 h to obtain dispersion B;
[0084] (3) Ammonia water was added dropwise to adjust the pH to 4.0, and 8 g of polydopamine and 0.25 g of conductive carbon black were added in sequence and ultrasonically dispersed uniformly; then 0.25 g of γ-aminopropyltriethoxysilane and 15 g of micron silicon (particle size D50: 0.5-2 μm) were added in sequence and ultrasonically dispersed uniformly, and stirred at room temperature for 2 h to obtain dispersion C;
[0085] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 170° C., to obtain a silicon-carbon precursor D;
[0086] (5) A plasma enhanced vapor deposition furnace is used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 5°C / min. The product is carbonized at 850°C for 2h, and then a 5% acetylene / nitrogen mixed gas is introduced and deposited at 500°C for 0.5h to obtain a spherical silicon-carbon product E. The product is then dispersed in deionized water, the solid content is adjusted to 10%, and the product is washed four times for 0.5h each time. The product is then filtered and dried to obtain a silicon-carbon negative electrode material.
[0087] Comparative Example 1
[0088] The preparation method of the silicon-carbon negative electrode material in this comparative example is different from that in Example 1 in that no ionic liquid is added in step (2), and the remaining steps are the same, and the steps are as follows:
[0089] (1) 5 g of cotton cellulose (purity 95%, particle size D50 30 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 2 h, and then treated in a sand mill with 0.3 mm zirconium oxide beads for 2 h to obtain dispersion A;
[0090] (2) adding 0.2 g of zinc chloride to dispersion A, adding oxalic acid solution to adjust the pH to 1.0, and stirring at 60° C. for 2 h to obtain dispersion B;
[0091] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 6 g of chitosan and 0.1 g of single-walled carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.15 g of γ-aminopropyltriethoxysilane and 15 g of nano-silicon (particle size D50: 50-150 nm) were added in sequence, ultrasonically dispersed uniformly, and stirred at room temperature for 2 h to obtain dispersion C;
[0092] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 180° C., to obtain a silicon-carbon precursor D;
[0093] (5) A plasma enhanced vapor deposition furnace was used to perform high-temperature carbonization sintering on the silicon-carbon precursor D at a heating rate of 5°C / min. The product was carbonized at 800°C for 2h, and then a 5% acetylene / nitrogen mixed gas was introduced and deposited at 500°C for 0.5h to obtain a spherical silicon-carbon product E. The product was then dispersed in deionized water and the solid content was adjusted to 10%. The product was washed three times for 0.5h each time, filtered and dried to obtain a silicon-carbon negative electrode material.
[0094] Comparative Example 2
[0095] The preparation method of the silicon-carbon negative electrode material in this comparative example is different from that in Example 1 in that the 5% acetylene / nitrogen mixed gas deposition is not performed in step (5), and the remaining steps are the same, and the steps are as follows:
[0096] (1) 5 g of cotton cellulose (purity 95%, particle size D50 30 μm) was added to 200 mL of deionized water, stirred and treated with high-energy ultrasound for 1 h, and then treated in a sand mill with 0.3 mm zirconium oxide beads for 2 h to obtain dispersion A;
[0097] (2) adding 0.2 g of zinc chloride and 0.2 g of 1-ethyl-3-methylimidazolium acetate to dispersion A, adding oxalic acid solution to adjust the pH to 1.0, and stirring at 60° C. for 2 h to obtain dispersion B;
[0098] (3) Ammonia water was added dropwise to adjust the pH to 3.0, and 6 g of chitosan and 0.1 g of single-walled carbon nanotubes were added in sequence and ultrasonically dispersed uniformly; then 0.15 g of γ-aminopropyltriethoxysilane and 15 g of nano-silicon (particle size D50: 50-150 nm) were added in sequence, ultrasonically dispersed uniformly, and stirred at room temperature for 2 h to obtain dispersion C;
[0099] (4) spray drying the dispersion C, adjusting the spray drying pressure to 0.2 MPa and the inlet temperature to 180° C., to obtain a silicon-carbon precursor D;
[0100] (5) The silicon-carbon precursor D is subjected to high-temperature carbonization sintering in a plasma enhanced vapor deposition furnace at a heating rate of 5°C / min and carbonized at 800°C for 2h to obtain a spherical silicon-carbon product E; the product is then dispersed in deionized water, the solid content is adjusted to 10%, and the product is washed three times for 0.5h each time, filtered and dried to obtain a silicon-carbon negative electrode material.
[0101] Application Examples
[0102] The silicon-carbon negative electrode material prepared by the present invention is mixed with the conductive agent carbon black and the binder (PAA) in a mass ratio of 8:1:1 to form a slurry, which is evenly coated on a copper foil and dried to form an electrode. The electrolyte is 1.0 mol L -1 LiPF 6The mixed organic solution is made of EC:DEC:DMC (mass ratio is 1:1:1) as solvent and 10% FEC as additive. The separator is a microporous polypropylene separator and the positive electrode is a lithium sheet, which is processed into a CR2032 button battery.
[0103] (1)Battery initial performance
[0104] The first cycle discharge test uses 100mA / g to discharge to 0.005V and then charge to 2.0V. Figure 4 This is the first charge and discharge diagram of the nanocellulose-based silicon-carbon negative electrode material obtained in Example 1 and the comparative example. It can be seen that the first charge specific capacity of the battery assembled from the material prepared in Example 1 reaches 1956.6 mAh / g, and the first efficiency is 91.5%. The capacity and first efficiency of the materials in Comparative Examples 1 and 2 are both much lower than those in Example 1. In addition, the first efficiency data of each example are shown in Table 1.
[0105] Table 1
[0106] First charge specific capacity (mAh / g) First effect (%) Example 1 1956.6 91.5 Example 2 1346.5 83.2 Example 3 1852.3 90.4 Example 4 1246.5 83.5 Example 5 1918.6 90.5 Example 6 1752.7 87.3 Example 7 2086.3 90.8 Comparative Example 1 1823.3 86.5 Comparative Example 2 1756.3 84.4
[0107] It can be seen from the table that the silicon-carbon negative electrode material prepared in Example 1 exerts a higher capacity and first coulombic efficiency, and Figure 2 It can be seen that the material has good spherical particles and forms a pore structure from the inside to the outside. The scheme of the present invention can still exert a high coulombic efficiency for the silicon oxygen raw material with low initial coulombic efficiency, as shown in Examples 2, 4 and 6. In Comparative Example 1, no ionic liquid was added, and the obtained cellulose product had a poor degree of nano-crystallization. During the spray drying process, the cellulose was greatly inhibited from forming a ball, and after sintering, the cellulose was formed as shown in FIG. Figure 3 The relatively dispersed broken particles shown. Figure 4 , Figure 5 It can be seen from the first charge and discharge diagrams and cycle diagrams of Example 1 and Comparative Examples 1 and 2 that the dispersed structure of Comparative Example 1 and the lack of secondary conductive carbon modification on the surface of Comparative Example 2 will result in a lower first efficiency. During the cycle, the silicon-carbon material of Comparative Example 1 is prone to cause electrode cracking, and the silicon-carbon material of Comparative Example 2 will also break and fail without the constraint of the surface carbon layer. Therefore, the cycle stability is poorer than that of Example 1.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material based on nanocellulose, characterized in that: Here are the steps: (1) Add cellulose to deionized water, stir and treat with high-energy ultrasound, and then grind to obtain dispersion A; (2) adding a hydrolysis catalyst and an ionic liquid to dispersion A, adding an acid solution to adjust the pH to 1.0-2.0, and heating and stirring to obtain dispersion B; (3) After adjusting the pH of dispersion B to 3.0-4.0, a carbon source and a conductive agent are added; then a coupling agent and a silicon source are added, and dispersion C is obtained after dispersion; (4) The dispersion C is spray dried to obtain a silicon-carbon precursor D; (5) The silicon-carbon precursor D is sintered in nitrogen and subjected to vapor deposition carbonization sintering to obtain a silicon-carbon product E; and then, after washing and drying, a silicon-carbon negative electrode material is obtained.
2. The method for preparing a nanocellulose-based silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (1), the cellulose is any one of cotton cellulose, wheat straw cellulose and corn straw cellulose, with a purity of 90-95% and a particle size D50 of 30-65 μm; and the high-energy ultrasonic treatment time is 1-4 h.
3. The method for preparing a nanocellulose-based silicon-carbon negative electrode material according to claim 2, characterized in that: In step (2), the hydrolysis catalyst is any one of zinc chloride, ferric chloride, nickel chloride, cobalt chloride, zinc nitrate, nickel nitrate, cobalt acetate and nickel acetate; the ionic liquid is any one of 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium hydrogen sulfate and 3-ethoxymethyl-1-methylimine hydrogen sulfate.
4. The method for preparing a silicon-carbon negative electrode material based on nanocellulose according to claim 3, characterized in that: The temperature of the heating and stirring treatment in step (2) is 60-90° C. and the time is 2-8 hours.
5. The method for preparing a silicon-carbon negative electrode material based on nanocellulose according to claim 4, characterized in that: The mass ratio of cellulose, carbon source, conductive agent, coupling agent and silicon source in the dispersion C of step (3) is 5: (6-8): (0.1-0.25): (0.15-0.5): (7.5-15); the concentration of the carbon source is 30-40 g / L.
6. The method for preparing the nanocellulose-based silicon-carbon negative electrode material according to claim 5, characterized in that: In step (3), the carbon source is any one of chitosan, citric acid, phytic acid, sucrose, polyethylene glycol, phenolic resin, polydopamine and fructose; the conductive agent is any one of single-walled or multi-walled carbon nanotubes, hydroxyl carbon nanotubes, carboxyl carbon nanotubes, graphene oxide, graphene, conductive carbon black and acetylene black; the coupling agent is any one of γ-aminopropyltriethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, N1-(3-(trimethoxysilyl)propyl)ethane-1,2-diamine, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and hexadecyltrimethylammonium bromide; and the silicon source is at least one of silicon oxide, nano-silicon and micro-silicon.
7. The method for preparing a silicon-carbon negative electrode material based on nanocellulose according to claim 6, characterized in that: In the step (4), the spray drying spray pressure is 0.15-0.25 MPa, and the inlet temperature is 160-200°C.
8. The method for preparing the nanocellulose-based silicon-carbon negative electrode material according to claim 7, characterized in that: In the step (5), the sintering in nitrogen is carried out by heating the temperature to 700-1000°C at a heating rate of 3-15°C / min and keeping the temperature for 2-6 hours. The deposition gas source in the vapor deposition carbonization sintering is a mixed gas composed of at least one of acetylene, ethylene, methane and ethane and nitrogen. The vapor deposition carbonization sintering temperature is 500-800°C and the time is 0.5-2 hours.
9. A silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The silicon-carbon negative electrode material has a pore structure from inside to outside.
10. A lithium ion battery, characterized in that: Including the silicon-carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Silicon-carbon composite material as well as preparation method and application thereof
CN114824234A
In-situ preparation method of cellulose-silicon dioxide composite aerogel
CN104448397A
High-capacity silicon-carbon material for lithium battery negative electrode and preparation method
CN112234182A
Graphitized porous silicon carbon negative electrode material, preparation method thereof and lithium ion battery
CN115642233A
Novel silicon-based negative electrode material and preparation method thereof
CN117525366A
Cited By
Silicon-carbon negative electrode composite preparation process for in-situ growth of nano silicon particles
CN120607238A
Porous carbon composite material and preparation method thereof
CN120646829A
Preparation method of silicon-containing silicon oxide-phenolic resin-artificial graphite composite negative electrode material
CN121355241A
Porous carbon carrier and preparation method thereof, silicon-carbon composite material and preparation method thereof, and battery
CN121709619A